FITOREMEDIASI LIMBAH MENGANDUNG TIMBAL (Pb) DAN NIKEL (Ni) MENGGUNAKAN TANAMAN KIAMBANG (Salvinia molesta) - Bunga Rulita Viobeth (Jurnal Teknik Lingkungan, 2013)
This research has been conducted on phytoremediation of waste containing lead (Pb) and nickel (Ni) using Kiambang (Salvinia molesta). Previous s studies by Teguh showed that Kiambang capable for reducing nickel content in the media phytoremediation with reduced nickel metal ion in 6 mg/L be reached until 2.36 mg/L fir 12 days. This study aims to determine the magnitude of decrease the concentration of lead and nickel in wastewater using Kiambang. Phytoremediation media of lead in the form a solution of 0.5 mg/L and 0.8 mg/L. A solution of Nickel at 2.5 mg/L and 3 mg/l. Each concentration included in 3 reactors with each reactor volume of 3 liters. Kiambang inserted into two reactors with a wet weight of each reactor at 30 gram and 60 grams. The reactor used as a reactor control. Concentration measurements of Pb and Ni on 3, 6, 9, 12 using AAS. The results showed that Kiambang is more better to decrease concentration of nickel than decrease of lead concentration. The final result concentration of Pb 0.5 mg/L with Kiambang wet weight 30; 60 grams are 0.412 mg/L and 0.304 mg/L. Then the final decrease of nickel concentration 3 mg/L is 0.670 mg/L; 0.252 mg/L. Kiambang can be categorized as metal accumulator species.